Production of SBS Reinforced Polyester Composite: Characterization of Physical and Chemical Properties - Şahal, Hakan; Aydoğmuş, Ercan (Turkish Chemical Society, 2023)
In this study, dissolved styrene butadiene styrene (SBS) copolymer is homogeneously reinforced into orthophthalic unsaturated polyester (UP) resin. Polyester composite production is carried out with the help of methyl ethyl ketone peroxide (MEKP) and cobalt octoate (Co Oc) catalysts. The density, Shore D hardness, thermal conductivity coefficient, thermal stability, morphological surface structure, and chemical bond structure of the obtained composite have been examined. According to the results, SBS reinforcement decreases the density of the composite and increases the thermal conductivity coefficient. The addition of SBS at different weight ratios (1%, 3%, 5%, 7%, and 10% w/w) reduces both the hardness and thermal stability of the polyester composite. According to the test and analysis results, 5 wt.% SBS reinforced polyester composite production is determined as the optimum ratio. 7 wt.% and above SBS reinforcement negatively affect the physical and chemical properties of the obtained composite. For example, when 10 wt. % SBS reinforced composite is examined by scanning electron microscope (SEM), and irregular pores are observed in the surface morphology. Also, it is understood by Fourier transform infrared spectroscopy (FTIR) that there is a physical interaction between SBS and polyester and that no chemical bond is formed. The thermal decomposition behavior of the composite has been determined according to the decrease in the activation energy. As SBS ratio increases, it is understood that the thermal stability of the product obtained with the decrease in the activation energy of the polyester composite weakens. © 2023, Turkish Chemical Society. All rights reserved.
Keywords: Activation energy; density; hardness; polyester composite; SBS; thermal conductivity